A Theoretical Analysis of Approaches to Enhance Students’ Grit and Academic Engagement - Qiao, Rui (Frontiers in Psychology, 2022)
The role of teachers in developing positive traits in EFL students has been widely endorsed in the literature. Two such traits that have pivotal roles in language teaching and learning are grit and academic engagement. Despite the proliferation of correlational studies on these constructs, theoretical and systematic review studies on the role of EFL teachers’ approaches in strengthening and enhancing these variables are scant. To fill this wide gap, the present study aimed to review the theoretical and empirical underpinnings of students’ grit and engagement and their teachability. In so doing, the definitions, conceptualizations, and dimensions of the two variables were presented. Moreover, a number of practical teaching approaches were suggested to EFL teachers in various contexts. Finally, implications, research gaps, and future directions of this research strand are provided to enhance EFL stakeholders’ knowledge of teachability of grit, engagement, and many other positive psychological traits.